REDEFINING AND REPOSITIONING ACTION RESEARCH IN SCHOOL PRACTICE - Nanik Retnowati (ENGLISH, 2020)
Classroom action research is undoubtedly important to be implemented by teachers. Many experts on education have provided enormous rationale bases for the benefits of conducting action research for quality education. However, there have not been many teachers performing it with many different reasons. It is important for any parties who are concerned on quality education to find out teachers’ reasons of not conducting action research. The data could be used to formulate any strategies to promote action research in school practice. However, this paper suggests that finding out why teachers perform action research is not less important. Teachers’ motives of performing action research cannot be separated from the values proposed by idealized concept of action research itself.  Thus it is important to examine closely whether teachers’ perspectives meet with the intended benefits as proposed theoretically.  The findings are useful to give an insight on whether action research needs to be redefined and repositioned in educational practice.